SIGNIFIKANSI PENGUASAAN GURU TERHADAP PSIKOLOGI SISWA DALAM PROSES BELAJAR MENGAJAR - RATNAWATI, RATNAWATI (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2017)
AbstrakA teacher in the process of teaching learning is one of the very influancer factor in gaining the purpose of teaching learning. In this contects, teacher is a giver and performer of the teaching learning. In performing his profession a teacher needs very much some variaty of up to date psychology according to development era and technology for development psychology is a knowledge which teachs equality and difference of psyche function as long as life, as like teaching about thinking process of children in one, two or five years old and how personality of some one changes and develops from children, adolecense to adult.The rule of teacher in developing studentspsychis that covered internal and external aspects is very signifcant. Because of students facedby a teacher hasdifferents cultural and educational backgrounds either internal or external, a techer as a educator is not possible to threat them without caring all of thir differentiations.  Teachers mastering of students’ psychis is very significant due to for a teacher who conducts his duties as educator and teacher with determainedpotentions and createrias, making teaching learning process effectively and efficiantly.